2011
DOI: 10.1152/physiolgenomics.00100.2011
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic and metabolomic analysis of fenofibrate and fish oil treatments in mice

Abstract: Elevated circulating triglycerides, which are considered a risk factor for cardiovascular disease, can be targeted by treatment with fenofibrate or fish oil. To gain insight into underlying mechanisms, we carried out a comparative transcriptomics and metabolomics analysis of the effect of 2 wk treatment with fenofibrate and fish oil in mice. Plasma triglycerides were significantly decreased by fenofibrate (-49.1%) and fish oil (-21.8%), whereas plasma cholesterol was increased by fenofibrate (+29.9%) and decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 70 publications
7
35
5
Order By: Relevance
“…Importantly, these effects of n-3 PUFAs have been shown to be independent of PPARα, as the suppression of SREBP1 and lipogenic gene expression by FO still occurs in liver of PPARα knockout mice4041. In contrast to the effects of FO, other studies have reported that pharmacological PPARα activation promotes the expression of lipogenic enzymes434445, and the findings of the current study, as well as those in a recent report comparing the PPARα agonist fenofibrate and FO, demonstrate that n-3 PUFA and PPARα activating compounds have opposing effects on a number of biosynthetic pathways, including FA synthesis46. Thus the lipid-lowering effect of FO in liver is not solely due to acceleration of fatty acid oxidation by PPARα activation and is likely also due to the influence of n-3 PUFAs on other signalling pathways.…”
Section: Discussionsupporting
confidence: 59%
“…Importantly, these effects of n-3 PUFAs have been shown to be independent of PPARα, as the suppression of SREBP1 and lipogenic gene expression by FO still occurs in liver of PPARα knockout mice4041. In contrast to the effects of FO, other studies have reported that pharmacological PPARα activation promotes the expression of lipogenic enzymes434445, and the findings of the current study, as well as those in a recent report comparing the PPARα agonist fenofibrate and FO, demonstrate that n-3 PUFA and PPARα activating compounds have opposing effects on a number of biosynthetic pathways, including FA synthesis46. Thus the lipid-lowering effect of FO in liver is not solely due to acceleration of fatty acid oxidation by PPARα activation and is likely also due to the influence of n-3 PUFAs on other signalling pathways.…”
Section: Discussionsupporting
confidence: 59%
“…Extensive gene-array profiling of the effects of the PPARα agonist ciprofibrate in the cynomolgus monkey showed the expected upregulation of fatty acid oxidation and mitochondrial oxidative phosphorylation, but also the strong downregulation of many targets in the complement and coagulation cascade [39] . The comple- 207 ment and coagulation cascade was also among the strongest negative targets of fenofibrate in mice [40] , and was also repressed by clofibrate, Wy-14,643 and gemfibrozil in rats [41] . Bile acid signaling and coagulation seem quite unrelated.…”
Section: Do Fxr and Pparα Regulate Secretion?mentioning
confidence: 97%
“…A better understanding of PPARa regulation by different nutritional signals in healthy individuals and in MetS patients will allow the design of specific pharmacological therapies, simultaneously targeting different NASHtriggering factors. Moreover, to improve NASH, dietary strategies, such as n-3 PUFA supplementation may be considered to ameliorate steatosis and inflammation, by a mechanism that may partially rely on PPARa activation [148,149]. However, the efficacy of n-3 PUFA in the treatment of NASH in human subjects remains to be demonstrated.…”
Section: Key Pointsmentioning
confidence: 99%